Evaluation of recombinant Taenia multiceps HSP70 antigen in a dipstick-based rapid diagnostic test for ovine coenurosis - Gunyakti-Kilinc, Seyma; Celik, Figen; Kesik, Harun Kaya; Uslug, Muhammet; Simsek, Sami (Bmc, 2026)
Background Coenurus cerebralis, the larval stage of Taenia multiceps, causes coenurosis, a severe neurological disease in sheep associated with significant economic losses. Ante-mortem diagnosis remains difficult due to nonspecific clinical signs and the limited applicability of laboratory-based methods under field conditions. Heat shock protein 70 (HSP70) has previously shown promising immunoreactivity in laboratory assays, suggesting its potential as a diagnostic antigen.This study aimed to evaluate the format-dependent performance of a laboratory-validated recombinant antigen when translated into a dipstick-based rapid diagnostic assay for ovine coenurosis. Results Despite strong immunoreactivity in Western blot analysis, rTmHSP70 failed to generate a visible test line signal in the dipstick assay under all tested conditions. In contrast, a partially purified hydatid cyst antigen produced visible signals but also caused non-specific reactions and false-positive results. These findings demonstrate that rTmHSP70, although suitable for laboratory-based assays, is not compatible with dipstick-format rapid diagnostics. Conclusion The study underscores the importance of assay format compatibility, antigen purity, and epitope accessibility in the development of reliable field-applicable diagnostic tests for coenurosis. The findings demonstrate that strong immunoreactivity in laboratory-based assays does not necessarily translate into functionality in rapid diagnostic formats, highlighting critical format-dependent limitations in assay development.
Keywords: Taenia multiceps; Coenurosis; HSP70; Dipstick test; Rapid diagnosis; Sheep